2022
DOI: 10.1101/2022.12.12.22283346
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating Subnational Excess Mortality in Times of Pandemic. An application to Frenchdépartementsin 2020

Abstract: The Covid-19 pandemic did not affect sub-national regions in a uniform way. Knowledge of the impact of the pandemic on mortality at the local level is therefore an important issue for better assessing its burden. Vital statistics are now available for an increasing number of countries for 2020 and 2021 and allow the calculation of sub-national excess mortality. However, this calculation faces two important methodological challenges: (1) it requires appropriate mortality projection models; (2) small populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Dealing with yearly mortality data, we place greater emphasis on refining the time windows employed in forecasting expected mortality in the absence of a pandemic. Sensitivity analyses and comparisons of various alternative approaches for estimating baseline mortality levels have been proposed across diverse data structures [36, 37, 38, 39]. Exploring these alternatives could provide additional insights.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dealing with yearly mortality data, we place greater emphasis on refining the time windows employed in forecasting expected mortality in the absence of a pandemic. Sensitivity analyses and comparisons of various alternative approaches for estimating baseline mortality levels have been proposed across diverse data structures [36, 37, 38, 39]. Exploring these alternatives could provide additional insights.…”
Section: Discussionmentioning
confidence: 99%
“…The starting year with the lowest deviance value was selected for the final analysis. More information about this approach can be found in [39].…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy that the whole procedure can be performed for any given age and regardless of the mortality indicator selected for estimating excess mortality (e.g., life expectancy or age-standardized death rate). More details on this approach can be found in [27]. All calculations are performed in R [32].…”
Section: Methodsmentioning
confidence: 99%
“…In dealing with small geographical areas, we focus on point-estimates as much as on uncertainty quantification. In order to obtain the mortality levels that would have been observed in 2020 in the absence of the pandemic, we took a robust forecasting approach that accounts for regional diversity and delivers analytic confidence intervals that account for all sources of uncertainty [27]. Furthermore, this study also identifies geographical clusters of high and low losses of life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…These national estimates, however, hide an uneven impact of the pandemic across subnational populations [8]. Indeed, previous studies have shown important inequalities in the mortality impact of COVID-19 by region [8][9][10][11][12], sex [13][14][15], socio-economic status [16][17][18], and race [17][18][19], and generally, higher case-fatality rates have been reported among older age groups [14,20]. Still, however, more work is needed to obtain a detailed picture of the mortality impact of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%